A dimensão geopolítica da sustentabilidade: uma cartografia da ação norueguesa no território brasileiro - Danilo Caporalli Barbosa (2019)
Environmental issues in the 20th and 21st Centuries have become more alarming than ever. Whether due to the anthropic action in the territory or to natural disasters, every day the environmental impacts have been perceived as global. On the other hand, the geopolitical relations among States, companies, Non-Governmental Organizations and Multilateral Agencies become decisive for the understanding of the more local issues. In this sense, 'sustainability' as a concept starts to figure and act under the territory as a result of global forces and disputes over hegemony. In the international scenario Norway stands out at the same time as a reference for sustainable development and exploitation of oil. These highlights together with exploration actions of aluminum in Brazilian soil, as well as the impacts of the contamination of the Pará River by mining tailings, indicate a possible contradiction between discourse and practice. Thus, in order to shed light on the territorial and political effects of this relationship in Brazil, the nexus between the two countries and their figurations in the global political environment are studied. We also present the historical context in which 'sustainability' emerges as a key concept for actions in territory, making it a singular object in the dispute of narratives and hegemony. Therefore, the cartographic method and the Actor-Network Theory are explored in order to map the controversies and the reports of actors imbricated in the dispute processes. By mapping a process, the text presented here follows a constant construction, as an account that continually traces a network. Thus, we try to understand and eventually dispute the narratives presented here.